Pengembangan Buku Guru Matematika SD Berbasis Kognisi - Widayati, Widayati; Mujidin, Mujidin (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
The books available can be said to be good, but there are still many teachers who have difficulty conveying the material to elementary school students. Many teachers also do not pay attention to children's cognitive development, so that mathematics learning is less enjoyable and students are less motivated. With the development of this Mathematics Teacher's Guidebook, it makes it easier for teachers to explain concepts from mathematics material. The aim of this research is to create a Grade 3 Mathematics Teacher's Guidebook, as well as determine the feasibility of the Mathematics Teacher's Guidebook. This research uses descriptive qualitative and quantitative methods. The instruments used in this research are the results of observations, teaching reflections, tests, questionnaires, Learning Implementation Plans (RPP). Qualitative data analysis techniques by reducing data refer to selecting, focusing, simplifying, abstracting and transforming